Bifidobacterium animalis subsp. lactis strains isolated from dog faeces - Bunešová, Věra; Vlková, Eva; Rada, Vojtěch; Ročková, Sárka; Svobodová, Ivona; Jebavý, Lukáš; Kmeť, Vladimír (Veterinary microbiology, 2012)
The aim of the study was to identify and characterize dog bifidobacterial isolates and compare them with commercial probiotic strains. Sixteen isolates of Bifidobacterium animalis ssp. lactis from dog faeces (German Shepherd Dog) were identified by subspecies-specific PCR, MALDI-TOF MS and sequencing. This study is the first describing B. animalis ssp. lactis occurring within the intestinal tract of dogs. Our dog isolates showed slightly different fingerprinting profiles obtained by RAPD-PCR and REP-PCR from those isolated from yogurt and type strains of B. animalis ssp. lactis. Both, dog and yogurt origin strains indicated survival in the simulated in vitro digestion assay and were resistant to low pH and bile salts. Moreover, strong auto-aggregation activity was observed only in dog origin B. animalis ssp. lactis strains. Dog strains showed good properties predicting their survival ability in GIT and could be tested as a potential new probiotics for dogs or other hosts.
Keywords: zvířata; Species Specificity; feces; Feces; Genetic Variation; Animals; střeva; DNA fingerprinting; psi; probiotika; ženské pohlaví; Probiotics; Intestines; technika náhodné amplifikace polymorfní DNA; druhová specificita; Random Amplified Polymorphic DNA Technique; Female; DNA Fingerprinting; Bifidobacterium; genetická variace; Dogs